Effects of cereal beta-glucan consumption on body weight, body mass index, waist circumference and total energy intake: A meta-analysis of randomized controlled trials. (April 2019) - Rahmani, Jamal; Miri, Ali; Černevičiūtė, Raminta; Thompson, Jacqueline; de Souza, Nurun Nisa; Sultana, Rehena; Kord Varkaneh, Hamed; Mousavi, Seyed Mohammad; Hekmatdoost, Azita
Highlights: Beta glucan consumption decreases body weight and BMI. The consumption of beta glucan did not affect the waist circumference and energy intake. Dosage of β-glucan≥ 4 g/day increased the amount of energy intake. Abstract: Background & objective(s): Obesity is a worldwide epidemic and a common medical condition associated with a variety of chronic diseases. Cereal beta-glucans are soluble fibers with potential health benefits. A number of randomized controlled trials (RCTs) have investigated the effect of cereal beta-glucan consumption on weight, but these results have not been summarized in a meta-analysis. The purpose of this study was to investigate the effect of cereal beta-glucan consumption on body weight, body mass index, waist circumference and a total energy intake. Methods: Studies were identified using MEDLINE/PubMed, Scopus and Cochrane databases. Screening of relevant articles and references was carried out until December 2018. There were no language restrictions. This systematic review and meta-analysis was performed using the Preferred Items for Reporting of Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: Twenty eligible studies were identified and analyzed. Our study found a significant reduction in body weight and body mass index (BMI) following beta-glucan consumption (weighted mean difference [WMD]: −0.77 kg, 95% CI: −1.49, −0.04) and (WMD: −0.62 kg/cm 2, 95% CI: −1.04, −0.21), respectively. There was no significant effect on waist circumference and energy intake. A subgroup analysis showed that a beta-glucan dose of ≥ 4 g/day lead to an increase in energy intake. Conclusion: The findings of this study indicates that cereal beta-glucan consumption seems to decrease body weight and BMI, but has no effect on waist circumference and energy intake.